A COMPARATIVE STUDY OF TEACHERS’ SELF-EFFICACY FOR TEACHING IN PRIMARY EDUCATION ACCORDING TO GENDER, YEARS OF TEACHING EXPERIENCE AND EDUCATIONAL BACKGROUND AT SIX CHURCH-BASED PRIMARY SCHOOLS IN NORTHERN SHAN STATE, MYANMAR - Brang San; González, Orlando Rafael González (Scholar: Human Sciences, 2022)
The purpose of this quantitative, comparative study was to determine if there were significant differences in teachers’ self-efficacy for teaching in primary education (in terms of efficacy for student engagement, instructional strategies and classroom management), according to their gender, years of teaching experience and educational background, at six purposively chosen church-based primary schools in Northern Shan State, Myanmar. The study was conducted on 127 teachers who were teaching at the target schools during the academic year 2020-2021. The Teachers’ Sense of Efficacy Scale (TSES, short form, Tschannen-Moran & Woolfolk Hoy, 2001) was used to measure the levels of self-efficacy for teaching in primary education including the three subscales (efficacy for student engagement, instructional strategies and classroom management). A total of 99 out of 127 (77%) teachers completed the questionnaire. After the data collection was done, descriptive statistics (means and standard deviations) and a statistical hypothesis testing (multiple analysis of variance, MANOVA) were carried out to address the research objectives and hypotheses of this study. The findings from this study revealed that there were no significant differences in teachers’ self-efficacy for teaching in primary education (in terms of efficacy for student engagement, instructional strategies and classroom management), according to their gender, years of teaching experience and educational background.